2017
DOI: 10.12738/estp.2017.2.0264
|View full text |Cite
|
Sign up to set email alerts
|

Korean Students’ Attitudes toward STEM Project-Based Learning and Major Selection

Abstract: Citation: Han, S. (2017). Korean students' attitudes toward STEM project-based learning and major selection. AbstractThe trend of avoiding science, technology, engineering, and mathematics (STEM) majors has persisted resulting in a lack of professionals in STEM fields. Further, the current STEM education system in Korea does not meet domestic demands for STEM labor. To discover an educational approach encouraging students to choose STEM majors at the post-secondary level, the current study employed a survey i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 29 publications
1
5
0
2
Order By: Relevance
“…Results in this study revealed that participants in the control group who learned physics through traditional instruction had not increased in sense making and effort in learning physics during the real study. Findings in this research are supported by previous studies in which traditional instruction leads students to memorize facts rather than make sense of information learned in class (Thomas, 2000;Han, 2017). Learning physics through traditional instruction, students passively listen, write down and summarize what the teacher says without thinking about the given information (Liu, 2014;Kortam et al, 2018;Aviyanti, 2020) and most of them are silent during the learning process (Hairan et al, 2018).…”
Section: Belief Specific Category -Sense Making and Effortsupporting
confidence: 82%
“…Results in this study revealed that participants in the control group who learned physics through traditional instruction had not increased in sense making and effort in learning physics during the real study. Findings in this research are supported by previous studies in which traditional instruction leads students to memorize facts rather than make sense of information learned in class (Thomas, 2000;Han, 2017). Learning physics through traditional instruction, students passively listen, write down and summarize what the teacher says without thinking about the given information (Liu, 2014;Kortam et al, 2018;Aviyanti, 2020) and most of them are silent during the learning process (Hairan et al, 2018).…”
Section: Belief Specific Category -Sense Making and Effortsupporting
confidence: 82%
“…This implies that DLP have higher benefit on language development than the learning of content subjects. Studies have also indicated that STEM field is less favoured by the students and there is a growing negative attitude towards learning science and mathematics (Kiemer, Groschner, Pehmer, & Seidel, 2015;Rice et al, 2013;Sunyoung, 2017). This calls for a serious consideration by the Ministry of Education in order to achieve the ratio of 60:40 in the number of students enrolled in the science stream and arts stream.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…STEM PjBL allow students to learn in groups, observe others while doing their own STEM projects, learn from their peers. The group work of STEM PjBL is aligned with social cognitive theory (Erdogan et al, 2016) which has direct relations with observation of others activities in social interactions and experiences (Han, 2017). In STEM PjBL, students have to follow several phases which define the problem from developing and testing the product in order to improve the product.…”
Section: B) Theoretical Frameworkmentioning
confidence: 99%